EKSPLORASI NILAI-NILAI PENDIDIKAN MATEMATIKA BERBASIS AYAT AL-QUR’AN DI SEKOLAH MENENGAH ATAS - Fahrul Huda; Agung Hartoyo; Sugiatno Sugiatno (Jurnal AlphaEuclidEdu, 2021)
Al-Qur'an verses can be used as a source of mathematics learning that contains the values of mathematics education, because, it can improve students' reasoning, application, mathematical skills, and student's personality. Therefore, the purpose of this study is to describe the results of the exploration of the values of mathematics education based on the verses of the Al-Qur'an, especially for the tenth grade of senior high school. The research method used is descriptive qualitative method with the form of research is library research. The research subjects were the Al-Qur'an verses and the mathematics function for tenth grade senior high school. The results showed that the values of mathematics education based on the verses of the Qur'an with mathematics functions for tenth grade students are found in surah Al Baqarah verse 184. From these verses, exploration of the values of mathematics education has been integrated with the core competencies of the curriculum 2013, so it is divided into two, formal values that contain spiritual and social aspects, and material values that contain knowledge and application aspects.             Keyword: Al-Qur'an verses, The values of mathematics education